Critical Care Ultrasound Competency of Fellows and Faculty in Pulmonary and Critical Care Medicine: A Nationwide Survey - Mark Adelman; Himanshu Deshwal; Deepak Pradhan (CINQUILL Medical Publishers Inc., 2023)
Purpose: Competency assessment standards for Critical Care Ultrasonography (CCUS) for Graduate Medical Education (GME) trainees in pulmonary/critical care medicine (PCCM) fellowship programs are lacking. We sought to answer the following research questions: How are PCCM fellows and teaching faculty assessed for CCUS competency? Which CCUS teaching methods are perceived as most effective by program directors (PDs) and fellows. Methods: Cross-sectional, nationwide, electronic survey of PCCM PDs and fellows in accredited GME training programs. Results: PDs and fellows both reported the highest rates of fellow competence to use CCUS for invasive procedural guidance, but lower rates for assessment of deep vein thrombosis and abdominal organs. 54% and 90% of PDs reported never assessing fellows or teaching faculty for CCUS competency, respectively. PDs and fellows perceived hands-on workshops and directly supervised CCUS exams as more effective learning methods than unsupervised CCUS archival with subsequent review and self-directed learning. Conclusions: There is substantial variation in CCUS competency assessment among PCCM fellows and teaching faculty nationwide. The majority of training programs do not formally assess fellows or teaching faculty for CCUS competence. Guidelines are needed to formulate standardized competency assessment tools for PCCM fellowship programs.